The study of coated carbide ball end milling tools on inconel 718 using numerical simulation analysis to attain cutting force and temperature predictive models at the cutting zone - Chien, S.; Reddy, M.; Lee, V.; Debnath, Sujan (2017)
The unique properties of Inconel 718 make it a challenging material to machine especially in ball end milling operations due to high cutting force and temperature concentrated at the cutting zone. These essentially lead to accelerated tool wear and failure resulting in high costs and loss of production. In this research, finite element numerical simulation was performed using AdvantEdge to simulate ball end milling using an 8mm TiAlN coated carbide tool. Response Surface Methodology (RSM) is applied by using a 3 level 3 factorial Box-Behnken design of experiment with different combinations of cutting speed, feed rate, and depth of cut parameters with a selected range of parameters to simulate finishing operations. Temperature contour from finite element analysis showed that the highest temperature occurs near the depth of cut line just before the chip separates from the workpiece. Using multiple linear regression, a quadratic polynomial model is developed for maximum cutting force and a linear polynomial model peak tool temperature response respectively. Analysis of Variance (ANOVA) showed that feed rate had the most significance for cutting force followed by depth of cut. Also, cutting speed was found to have little influence. For peak tool temperature, cutting speed was the most significant cutting parameter followed by feed rate and depth of cut.